Distributor intermediation in the farm to food service value chain. Issue 3 (16th January 2018) - Givens, Graham; Dunning, Rebecca
Abstract: Short food supply chains, such as those of fruit and vegetable farmers delivering fresh product directly to restaurants, promise potentially higher returns to primary producers by avoiding the expense of intermediary distributors. Direct farm-to-chef supply chains also present a lower barrier to entry for small and beginning farmers, who are often scaled-out of the restaurant market by the volume requirements of food service distributors. High transactions costs for direct exchange, however, impede growth in this type of market channel. This From the Field paper describes an ongoing initiative by a regional food service distributor to play an active and collaborative role in the farm to food service supply chain, acting as a value chain partner to identify produce items desired by chefs, supply this market intelligence to growers and to garner commitments from farmers to grow and chefs to buy these products in upcoming seasons. By the eighth month of the effort, the distributor had assigned one of its produce buyers to act as a local specialist, working directly with chefs and local growers; and had initiated a series of mini local food shows to provide chefs and growers opportunities for face-to-face communication. The ultimate objective—to garner product-specific commitments from chefs and from growers—remains a work in progress.